Competence and Work Discipline on Employee Performance at the Muara Enim Regency DPRD Secretariat - Tiara Audia; Dewi Brima Atika; Apandi (Institut Pemerintahan Dalam Negeri, 2025)
Employees are essential assets of an organization, serving as planners and controllers of institutional activities. In government institutions, high-performing employees are vital for achieving organizational goals. Among the factors influencing employee performance are competence and work discipline. This study aims to examine the extent to which competence and work discipline affect employee performance at the Secretariat Office of the Regional House of Representatives (DPRD) of Muara Enim Regency. The research employed an associative method with a quantitative approach. The population comprised 38 respondents, and a saturated sampling technique was applied, involving all civil servant employees at the DPRD Secretariat Office of Muara Enim Regency. The study findings reveal that: (1) competence positively influences employee performance, with a beta coefficient (β) of 0.108 and a contribution of 24.8%; (2) work discipline positively affects employee performance, with a beta coefficient (β) of 0.115 and a contribution of 21.2%; and (3) competence and work discipline jointly have a positive effect on employee performance, with a combined contribution of 33.1%, while the remaining 66.9% is influenced by other factors.